Komodifikasi Konten Video Talkshow dan Kuatnya Posisi Subjek di Media Youtube Menjawab Selera Pasar di Era Disrupsi - Hamanduna, Antonius Obed Lapu (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
The movement of broadcasting the Indonesia Lawyer Club (ILC) program, which was originally through conventional media channels, has now switched to the YouTube digital media platform with the name Podcast Karni Ilyas Club (KIC) to revive democracy and opportunities for citizens to channel their ideas and opinions discursively. In this era of disruption, video talk show content seems to respond to social needs that are faced with the pressure of market tastes and today's business competition. This has an impact on the quality of content production that moves quickly, effectively and efficiently. Therefore, on the one hand, the Karni Ilyas Club as a creator because it utilizes this digital media platform, produces more discursive video content and invites contacts which of course has a more promising advantage. On the other hand, the high access of the Indonesian people to Youtube not only attracts the interest of companies that are advertisers, they are even in a subject position to build a community of creators on their platform. Researchers saw that the Karni Ilyas Club YouTube video content has occurred in the creators' creative process that has taken advantage of the negotiation of values ??between the creativity space, the self-expression of the audience and the creator as well as the company's interest to activate it on the KIC Podcast. However, it should be noted that openness in the context of this society, direct monitoring of Youtube media as a social platform for monitoring its existence to continue to benefit from the speed of capital rotation based on capitalist interests.